Sufficient conditions for the existence of the $υ$ -density for zeros of entire function of order zero - Zabolotskii, N. V.; Mostova, M. R. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We select the subclasses of zero-order entire functions $f$ for which we present sufficient conditions for the existence of $υ$ -density for zeros of $f$ in terms of the asymptotic behavior of the logarithmic derivative F and regular growth of theFourier coefficients of $F$.